Readings on The grapes of wrath - Wiener, Gary (San Diego, CA : Greenhaven, 1999)
A comprehensive guide which includes biographical and critical information in an easy-to-understand format.
Includes bibliographical references and index.
10-A.
Keywords: Steinbeck, John, -- 1902-1968.; Steinbeck, John, -- 1902-1968.; Migrant agricultural laborers in literature; Labor camps in literature; Migrant labor in literature; California in literature; California -- In literature